IDENTIFICATION LOCAL ISOLATES OF Trichophyton mentagrophytes AND DETECTION OF KERATINASE GENE USING PCR TECHNIQUE - & et al., Abbas (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to identify dermatophytic selective isolate using PCR technique as a rapid molecular assay. The results of this study showed among 60 samples of patients suffering from ringworm disease. forty isolates (66%) were Trichophyton mentagrophytes which diagnosed as dermatophytosis according to morphological and cultural methods. In order to investigate the ability of isolates to keratin analyses using solid medium supplemented with keratin azure , the results revealed that 20 isolates appeared best ability to keratin analysis and nine isolates had best ability for keratinase production in submerged culture. According to this results T. mantagrophytes (K3) (had higher activity for keratinase) was chosen for molecular identification. The results of PCR revealed that primer for18S rRNA gene of T. mentagrophytes K1 isolate and specific primer for subtilisin like protease gene were amplified and appeared as single DNA band with a molecular base of 690 bp and 623bp respectively .The blast result of sample sequences of amplified fragment revealed that the isolate were 100% identical to reference sequence of T.mentagrophytes var. interdigtal and depending on data base in NCBI The result of PCR product for enzyme showed new type named GBF60362 (402) subtilisin-like protease related to T. mentagrophytes 1354684064 BFBSOLP00892.